Optimal model of the combined cooling, heating, and power system by improved arithmetic optimization algorithm - Guo, Haibing; Sun, Zhi; Sun, Haixia; Ebrahimian, Homayoun (Energy sources. Part A, Recovery, utilization, and environmental effects, 2025)
Due to the scarcity of energy sources, there is a requirement for a system that, besides saving energy, produces energy on its own. One way to meet this need is to utilize combined cooling, heating, and power (CCHP) systems. The CCHP system is the concurrent and thermodynamic production of two or more energy forms from a clear initial origin. However, the method of determining the chiller properly and the power generation unit capacity is always one of the problems for optimal designing of the CCHP systems. In this study, a new optimized model of the yearly hourly dynamic simulation is proposed for a CCHP system. To get better results, a newly developed design of the newly presented Arithmetic Optimizer Algorithm is designed and conducted. Afterward, the suggested improved Arithmetic Optimizer was selected to optimize the CCHP system for its installed volume. The proposed method is confirmed by a case study from a main business region of Nanjing, China. The final analysis is done by comparison of the method with the real CCHP system, which indicates a proper satisfaction between them. The project has been established by considering a 4260 kW absorption chiller and a 4000-kW engine installed capacity. The power generation unit installed capacity is obtained 1321 kW during the variations of the CDER, PES, and LCCR indexes in various absorption cooling to the highest ratio of cooling load. By improving the absorption chiller installed capacity from 0.1 to 0.6, the CEI is increased. By exceeding the power above 5000 kW, the life cycle cost reduction has been anticipated to be less than 0. Also, simulation results indicate that different results can be obtained by different indexes.